2011
DOI: 10.1111/j.1472-8206.2010.00825.x
|View full text |Cite
|
Sign up to set email alerts
|

Lithium decreased endothelium‐mediated, but not nonadrenergic noncholinergic, relaxation of guinea pig corpus cavernosum in vitro: a role for nitrergic system

Abstract: Lithium causes erectile dysfunction in patients but its mechanism is yet unknown. The aim of our study was to verify the effect of acute lithium administration on the nonadrenergic noncholinergic (NANC)- and endothelium-mediated relaxation of guinea pig isolated corpus cavernosum. Although lithium (0.5, 1, and 5mm) had no effect on the neurogenic relaxations, it significantly (P<0.001) attenuated the relaxant responses to acetylcholine in a concentration-dependent manner. Combination of low concentration of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Lithium, valproate, carbamazepine (CBZ), and second-generation antipsychotics (e.g., olanzapine) are effective for the treatment of acute manic episodes [1,2]. However, some patients fail to respond adequately to these treatments, and the adverse effects of these drugs might limit their use or reduce adherence to treatment [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Lithium, valproate, carbamazepine (CBZ), and second-generation antipsychotics (e.g., olanzapine) are effective for the treatment of acute manic episodes [1,2]. However, some patients fail to respond adequately to these treatments, and the adverse effects of these drugs might limit their use or reduce adherence to treatment [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Penile erection occurs as a consequence of cavernosal smooth muscle relaxation, in which NO seems to play a central role . Lithium probably causes erectile dysfunction through impairment of endothelial‐mediated relaxation of the corpus cavernosa . This effect of lithium might be related to its regulatory effect on phosphoinositol‐linked second messengers , as the activity of the phosphoinositol cycle in the endothelium of the corpus cavernosum is a crucial step in NO production .…”
Section: Discussionmentioning
confidence: 99%
“…However, lithium can negatively affect several organs, including the kidneys, thyroid gland, and skin (6,7). Several studies have also suggested a negative effect of lithium on sexual function (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Although the frequency of the sexual side effects of lithium is lower than that of selective serotonin reuptake inhibitors, it is still high enough to warrant further consideration.…”
Section: Objectivesmentioning
confidence: 99%
See 2 more Smart Citations